Berbahasa Inggris Melalui Teater Wayang - Eddy Pursubaryanto (Gelar : Jurnal Seni Budaya, 2007)
This article presents an example of how a script of Wayang Kulit in English version  is used to provide more English exposure for English learners. It offers a strategy for  English instructors and anyone who is learning English.